2011
DOI: 10.1089/jmf.2010.0196
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Green Tea Extract Against Cariogenic Microflora: An In Vivo Study

Abstract: The aim of the present study was to test in vivo the effectiveness of an experimental green tea extract in reducing levels of mutans streptococci and lactobacilli in saliva by means of selective culture medium. Sixty-six healthy patients ranging in age from 12 to 18 years were recruited and randomly divided into two groups: Group A (n=33) and group B (n=33). Group A subjects were asked to rinse their mouths with 40 mL of an experimental green tea extract, for 1 minute, three times a day for a week, whereas Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 20 publications
5
56
0
14
Order By: Relevance
“…There are previous published studies on the activity of tea components against bacteria responsible for oral diseases. Some research groups showed that tea extracts inhibited the attachment of bacteria to oral surfaces [32] and are effective against cariogenic microorganisms [23]. It was observed that rinsing the mouth with green tea led to a significant reduction of cariogenic bacteria like S. mutans and Lactobacillus [19,33].…”
Section: Microbiological Assays – Determination Of Minimum Inhibitorymentioning
confidence: 99%
“…There are previous published studies on the activity of tea components against bacteria responsible for oral diseases. Some research groups showed that tea extracts inhibited the attachment of bacteria to oral surfaces [32] and are effective against cariogenic microorganisms [23]. It was observed that rinsing the mouth with green tea led to a significant reduction of cariogenic bacteria like S. mutans and Lactobacillus [19,33].…”
Section: Microbiological Assays – Determination Of Minimum Inhibitorymentioning
confidence: 99%
“…Ferrazzano et al, 21 in their in vivo study, evaluated the antimicrobial effect of green tea extract on cariogenic microflora. Since varnish provides longer exposure than solutions and mouthrinses 22,23 and considering the lack of information on the efficacy of green tea varnish on caries formation, this study sought to assess the effect of green tea varnish on the depth of root caries.…”
Section: 5005/jp-journals-10024-2227mentioning
confidence: 99%
“…This comprises antioxidant, antibacterial, antiviral, anti-allergic, anti-colitis, anti-inflammatory, anti-arthritic and anti-cancer activities [21][22][23][24][25] . Among several polyphenol sources in the human diet, tea is one of the most consumed beverages around the world as a result of the pleasant taste, attractive aroma and health-promoting effects.…”
Section: Health Benefits Of Tea Polyphenols As Dietary Natural Productsmentioning
confidence: 99%